Distinguishing multiple lung primaries from intra-pulmonary metastases and treatment implications. Issue 11 (1st November 2020) - Voulaz, Emanuele; Novellis, Pierluigi; Rossetti, Francesca; Solinas, Michela; Rossi, Sabrina; Alloisio, Marco; Pelosi, Giuseppe; Veronesi, Giulia
ABSTRACT: Introduction: The distinction between multiple primary lung cancers and intra-pulmonary metastases has been extensively investigated because of its important clinical and therapeutic implications. Areas covered: Rapidly improving imaging technology and genomic analysis has led to a finer discrimination between multiple primary lung tumors and pulmonary metastases. However, over the past few decades, standardized criteria for the identification of multiple lung tumors have been lacking. Therefore, in 2017 a multidisciplinary international committee composed of the Union for International Cancer Control (UICC), American Joint Committee on Cancer (AJCC) and International Association for the Study of Lung Cancer (IASLC) addressed this problem when drawing up the 8th edition of TMN stage classification, that now represents a specific consensus on this topic. The most advanced diagnostic strategies associated with screening allow for the detection of early stage synchronous lung cancers. Expert opinion: Although diagnostic confirmation relies on pathologic and clinical examination, new molecular analyses help in the discrimination between primary and secondary tumors. The treatment of multiple primary lung tumors remains, whenever possible, a local treatment based on surgical resection, providing the absence of distant or local (lymph node) metastases.